2016
DOI: 10.1086/688847
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Methods in Pulmonary Hypertension Phenotyping in the Age of Precision Medicine (2015 Grover Conference Series)

Abstract: Among pulmonary vascular diseases, pulmonary hypertension (PH) is the best studied and has been the focus of our work. The current classification of PH is based on a relatively simple combination of patient characteristics and hemodynamics. This leads to inherent limitations, including the inability to customize treatment and the lack of clarity from a more granular identification based on individual patient phenotypes. Accurate phenotyping of PH can be used in the clinic to select therapies and determine prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 96 publications
(139 reference statements)
0
13
0
Order By: Relevance
“…Currently, there are no established ways to test certain mechanisms of disease in a patient with PAH. We have previously shown that the cutaneous microvascular response to treprostinil iontophoresis is reduced in patients with idiopathic PAH compared to controls (9) supporting that abnormalities in the pulmonary vasomotor biology may be associated with alterations in the cutaneous microvascular vasodilatory response (10). Several other studies have shown evidence of extrapulmonary vascular involvement in PAH (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 81%
“…Currently, there are no established ways to test certain mechanisms of disease in a patient with PAH. We have previously shown that the cutaneous microvascular response to treprostinil iontophoresis is reduced in patients with idiopathic PAH compared to controls (9) supporting that abnormalities in the pulmonary vasomotor biology may be associated with alterations in the cutaneous microvascular vasodilatory response (10). Several other studies have shown evidence of extrapulmonary vascular involvement in PAH (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 81%
“…The current approach to treatment does not take into account recent and ongoing advances in genomics, metabolomics, imaging, etc. (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Pulmonary Hypertension and Precision Medicine Through The "Omentioning
confidence: 99%
“…Several nationally ranked teams of basic, translational, and clinical investigators with expertise in PVDs were awarded funds to (1): reclassify subsets of patients with PH regardless of the existing conventional World Health Organization classification system (2); define novel, clinically relevant therapeutic indices that may be useful for intermediate or primary outcomes in clinical trials (3); identify biomarkers of PH for detection and prevention research; and (4) define novel vascular disease phenotypes through endophenotyping approaches, including genomics, proteomics, metabolomics, etc. (5,14). Recently, these teams of experts convened a workshop with other NHLBI initiatives, patient advocacy organizations, regulatory agencies, and pharmaceutical industry experts to discuss current and prospective research priorities and their alignment with the NHLBI Strategic Vision on precision medicine for PVDs (Figure 1).…”
Section: Pulmonary Hypertension and Precision Medicine Through The "Omentioning
confidence: 99%
“…The World Health Organization classifies patients with PH into five groups on the basis of etiology (3). Multiple phenotypes such as vasoconstriction, dysregulated pulmonary vascular cell proliferation and remodeling, and inflammation contribute to the PH disease process (4-6) making therapeutic design complicated (7,8).…”
mentioning
confidence: 99%